2008
DOI: 10.1510/icvts.2007.173377
|View full text |Cite
|
Sign up to set email alerts
|

Awake subxyphoid minimally invasive direct coronary artery bypass grafting yielded minimum invasive cardiac surgery for high risk patients

Abstract: Off-pump coronary artery bypass graft (CABG) surgery has become a widely used modality and has received recognized as a minimally invasive surgery with few complications. However, for patients with severely impaired pulmonary function, further considerations have to be given to reduce the complications associated with general anesthesia. We have accumulated experience in awake off-pump surgery combined with high thoracic epidural anesthesia. In this report we describe the use of alternative subxiphoid approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Watanabe, et al 14) reported awake subxiphoid CABG in 3 patients with severe pulmonary dysfunction. A catheter for high thoracic epidural anesthesia was inserted 1 day before surgery, and under the appropriate amount of epidural anesthesia, the right gastroepiploic artery was harvested through a small subxiphoid incision, and the artery was anastomosed to the left anterior descending artery (LAD).…”
Section: Awake Opcabmentioning
confidence: 99%
“…Watanabe, et al 14) reported awake subxiphoid CABG in 3 patients with severe pulmonary dysfunction. A catheter for high thoracic epidural anesthesia was inserted 1 day before surgery, and under the appropriate amount of epidural anesthesia, the right gastroepiploic artery was harvested through a small subxiphoid incision, and the artery was anastomosed to the left anterior descending artery (LAD).…”
Section: Awake Opcabmentioning
confidence: 99%
“…Although cardiac surgery has lagged far behind other specialties in the development of robot-assisted minimally invasive surgery, significant advances have been made, and encouraging reports have emerged. [10][11][12][13] The superiority of ITA as a conduit has been well established for long-term patency and event-free survival. Robotic assistance has allowed BITA grafting to be performed through a minimally invasive access method.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, new surgical approaches usually contain a steep learning curve, 10 which could also be the case with the robot-assisted subxiphoid approach.…”
Section: Discussionmentioning
confidence: 99%
“…The awake coronary artery bypass graft is now a well-established technique, and it is known to decrease the adverse side effects typically associated with general anesthesia and mechanical ventilation. 11,14,16,17,23 Awake craniotomies have traditionally been performed for epilepsy surgery and neurooncological operations for tumors involving the eloquent cortex. 12,20 With the development of improved anesthetic techniques and more sophisticated neuronavigation equipment, awake craniotomy has become a fast, safe, and effective procedure with good patient tolerance.…”
Section: Discussionmentioning
confidence: 99%